Estimation of blue carbon stock in the Liaohe Estuary wetland based on soil thickness and multi-scenario modeling - Lina Ke; Nan Lei; Shilin Zhang; Changkun Yin; Yao Lu; Lei Wang; Qin Tan; Yu Zhao; Quanming Wang (Ecological Indicators)
Coastal wetlands are located in the ecotone between land and sea and are key areas for achieving the goals of “carbon peak” and “carbon neutrality.” They are crucial in mitigating marine pollution, regulating the climate, and balancing carbon budgets. This paper took the Liaohe Estuary wetland as the study area, combined with the distributional difference characteristics of soil carbon density in wetlands, constructed a wetland carbon density estimation method that improved the SoLIM model, and coupled the PLUS and InVEST models to achieve the fine estimation of wetland blue carbon stock under different simulation scenarios. The research analyzed the spatiotemporal distribution characteristics of land cover and blue carbon stock from 2000 to 2023. Additionally, the distribution of blue carbon stocks and their degradation and improvement were modeled for different scenarios in 2030. The results indicate that: (1) The soil thickness in the study area is generally distributed between 40 and 60 cm, with less distribution in the 60–80 cm and 20–40 cm intervals and the least in the 0–20 cm interval. Shallower soil thickness areas in wetlands were distributed near urban residential areas, while deeper soil thickness areas were in phragmites australis wetlands and tidal flat areas. (2) From 2000 to 2023, the wetland ecology in the study area was gradually restored. The area fraction of natural wetland tidal flat and suaeda salsa increased to 15.17 % and 3.69 %, respectively, while the area fraction of artificial wetland cropland and non-wetland bare land declined to 9.53 % and 0.39 %, respectively. In 2030, under the natural growth scenario (NGS), the expansion of the aquaculture ponds is the most obvious, while the shrinkage in suaeda salsa and shallow marine water areas is the most severe. Under the economic development scenario (EDS), the built-up land increases most significantly, and the phragmites australis and suaeda salsa decrease in different degrees. Compared with NGS and EDS, the natural wetland area under the ecological priority scenario (EPS) grew significantly. For example, from 2023 to 2030, the area of the suaeda salsa and river increased by 26.63 % and 20.09 %, respectively, indicating a significant restoration of the ecological status. (3) From 2000 to 2023, blue carbon stocks in the study area demonstrated an overall upward trend, yet with a progressively decelerating growth rate. The high-value regions of blue carbon stocks are predominantly situated in the northern section of the study area. The research area experienced an increase in blue carbon stock of 133.07 × 106 t under the NGS, 94.80 × 106 t under the EDS, and 150.62 × 106 t under the EPS. The EPS is the most conducive to the sequestration goal of the wetlands in the study area. The results of this paper provide a scientific basis for the sustainable management of coastal wetlands, offering ideas and references for the future fine accounting of carbon stock in coastal wetlands, as well as the scientific planning of negative carbon emissions.